(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
No nation is an island. Because domestic policies are constantly affected by developments outside, nations are compelled to (rather than sit on the fence or out-rightly isolate themselves) enter into dialogue with target or initiating entities or form alliance(s) for the purpose of enhancing their status quo, or increasing their power or prestige and survival in’ the international system.